The impact of potassium manganate (VII) on the effectiveness of coagulation in the removal of iron and manganese from groundwater with an increased content of organic substances = Wpływ mnanganianu (VII) potasu na skuteczność koagulacji w usuwaniu związków żelaza i manganu z wody podziemnej o podwyższonej zawartości substancji organicznych - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of studies concerning the impact of the method of Fe(II) ion oxidisation (dissolved oxygen and potassium manganate (VII)) on the effectiveness of coagulation in the removal of iron and manganese from groundwater with an increased content of organic substances.
Keywords: groundwaters; iron; manganese; organic substances; potassium manganate; coagulation; wody podziemne; żelazo; mangan; substancje organiczne; manganian potasu; koagulacja